ANALISA VISUAL DESAIN KARAKTER SERIAL ANIMASI “KUKU ROCK YOU” - Nadya Nadya (Universitas Bunda Mulia, 2021)
Nowadays, the influence of technological developments is increasingly rapid and widespread, especially in the creative industry. The cultivation of animated films is getting more serious, this can be seen from the maturity of the character design processing. One of them is created by Indonesian studio film, called “Kuku Rock You”. This three-dimensional animated film won in the Asiagraph competition in 2008. This comedy genre film tells the story of a native chicken who is obsessed with becoming a rock singer with a funny and unique story.The purpose of this research is to analyze the character design in the Kuku Rock You animated series. This research use holistic character design theory, so that the results of this research can be useful for animators or illustrators in creating a similar product. This research used qualitative methods that provide descriptive data about character designs that are theoretically capable of being iconic characters and are expected to be well received by the audience. The result of this research are a form of analysis of characters designs that exist in the Kuku Rock You series through a holistic character design theory approach.